Foreign Investment in the Czech Republic : Drivers of Attractiveness and Evolution of Foreign Ownership in Listed Companies - Panteleymonov, Dmytro (2025)
This thesis examines the determinants of foreign ownership in Czech listed companies and analyses how ownership structures have developed over the period 2014–2024. The study integrates macroeconomic indicators, firm-level financial characteristics, and market-segment information from the Prague Stock Exchange to identify the factors associated with ownership change. A combination of descriptive statistics, correlation analysis, and panel-data regression is employed to assess both external and internal drivers of investor behaviour. The research also compares differences across PSE market segments and evaluates the relevance of information asymmetry, market transparency and company size in shaping foreign investor decisions. The results show that ownership structures are highly persistent, with only limited sensitivity to short-term macroeconomic fluctuations, while firm-level indicators demonstrate economically meaningful but statistically modest effects. The findings highlight that foreign investor behaviour in the Czech market is shaped primarily by long-term structural factors rather than year-to-year financial performance.